2020
DOI: 10.12669/pjms.36.6.2947
|View full text |Cite
|
Sign up to set email alerts
|

Successful radio-frequency catheter ablation of two cases of supraventricular tachycardia via a left-sided inferior vena cava

Abstract: Congenital venous anomalies are uncommon, incidental findings encountered during adult interventional electrophysiology procedures. Femoral venous access is conventionally used during cardiac electrophysiology studies to gain access to the heart. The chance finding of an inferior vena cava anomaly may preclude the performance of these procedures from the femoral approach. We describe two cases in which we were able to successfully perform different radiofrequency catheter ablation procedures in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Some other studies from Pakistan by Awan RA et al, Shafquat A et al, and Shaikh SA et al showed that SVT due to any cause can be effectively treated by using radio frequency ablations nevertheless this invasive method required technical facilities and skill expertise which are not readily available in health care system of Pakistan, so by using MVM as used in our study SVT can be treated without involvement of surgical equipment and skills. [15][16][17] Regional studies by Huang EP et al in 2022, Lan Q et al in 2021and Abdulhamid AS et al in 2021 reported that by using MVM, the conversion rate of SVT to sinus rhythm was more effective than SVM showing that the result of our studies are consistent with their results. They also stated that use of MVM also reduced the use of anti-arrhythmic drugs, stay time in emergency department and adverse events.…”
Section: Methodssupporting
confidence: 87%
“…Some other studies from Pakistan by Awan RA et al, Shafquat A et al, and Shaikh SA et al showed that SVT due to any cause can be effectively treated by using radio frequency ablations nevertheless this invasive method required technical facilities and skill expertise which are not readily available in health care system of Pakistan, so by using MVM as used in our study SVT can be treated without involvement of surgical equipment and skills. [15][16][17] Regional studies by Huang EP et al in 2022, Lan Q et al in 2021and Abdulhamid AS et al in 2021 reported that by using MVM, the conversion rate of SVT to sinus rhythm was more effective than SVM showing that the result of our studies are consistent with their results. They also stated that use of MVM also reduced the use of anti-arrhythmic drugs, stay time in emergency department and adverse events.…”
Section: Methodssupporting
confidence: 87%